2017
DOI: 10.3389/fmicb.2017.01832
|View full text |Cite
|
Sign up to set email alerts
|

Legacy Effects on the Recovery of Soil Bacterial Communities from Extreme Temperature Perturbation

Abstract: The type and frequency of disturbances experienced by soil microbiomes is expected to increase given predicted global climate change scenarios and intensified anthropogenic pressures on ecosystems. While the direct effect of multiple disturbances to soil microbes has been explored in terms of function, their effect on the recovery of microbial community composition remains unclear. Here, we used soil microcosm experiments and multiple model disturbances to explore their short-term effect on the recovery of soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 58 publications
8
79
0
Order By: Relevance
“…Correspondingly, we found a higher abundance of carbon and nitrogen in organically managed soils, and higher phosphorus in conventionally-managed soils, in accordance with other studies of coffee agroecosystems in other countries (Partelli et al 2012). Differences in soil carbon, phosphorus, and nitrogen are strong determinants of bacterial community composition The previous land use of each farm had a strong effect on the soil microbiome, consistent with experimental findings of legacy effects on the assembly of soil microbial communities (Jurburg et al 2017;Peerawat et al 2018;Turley et al 2020). Our study further shows the persistent effect of previous land uses on lands under active cultivation.…”
Section: Discussionsupporting
confidence: 92%
“…Correspondingly, we found a higher abundance of carbon and nitrogen in organically managed soils, and higher phosphorus in conventionally-managed soils, in accordance with other studies of coffee agroecosystems in other countries (Partelli et al 2012). Differences in soil carbon, phosphorus, and nitrogen are strong determinants of bacterial community composition The previous land use of each farm had a strong effect on the soil microbiome, consistent with experimental findings of legacy effects on the assembly of soil microbial communities (Jurburg et al 2017;Peerawat et al 2018;Turley et al 2020). Our study further shows the persistent effect of previous land uses on lands under active cultivation.…”
Section: Discussionsupporting
confidence: 92%
“…were displaced within the first week after hatching by rapid-growing members of Clostridiales, whose abundance was in turn limited by the influx of diverse, specialist taxa associated with the adult broiler microbiome. Competition for resources has been previously proposed as a key component of microbial community assembly in various environments (Ho, Lüke, Reim, & Frenzel, 2016), and the temporal pattern of succession matches that observed in soils (Jurburg et al, 2017), suggesting that it may be related to the growth rates of various microbial community members. The measurement of resource availability in the GIT may aid in revealing the role of resource competition in successional dynamics in the broiler GIT.…”
Section: Discussionmentioning
confidence: 55%
“…Another experimental study also finds indications for cumulative effects, by assessing the recovery time of an aquatic microbial community with increasing number of disturbances (Garnier et al, 2017). Similarly, Jurburg et al (2017) observed multiplicative effects of various temperature shocks on the recovery of soil microbial communities. In our study, such collapses become more likely with increasing disturbance size (Figure 5).…”
Section: Discussionmentioning
confidence: 89%